Operabilidad y resecabilidad en el tratamiento del cáncer pulmonar en los años 1968, 1978 y 1988 - Della Torre, Horacio A (Cirugía del Uruguay, 1991)
The operability and resectability in the lung cancer population from Cetrángolo Hospital in 1968, 19 78, and 1988, was revised.